The immunotoxicity of aluminum trichloride on rat peritoneal macrophages via β2-adrenoceptors/cAMP pathway acted by norepinephrine. (April 2016) - Zhuang, Cuicui; Liu, Dawei; Yang, Xu; Wang, Haoran; Han, Lulu; Li, Yanfei
Abstract: The previous research found that norepinephrine (NE) enhanced the immunotoxicity of aluminum trichloride (AlCl3 ) on rat peritoneal macrophages in vitro through activating the β2 -adrenoceptors (β2 -AR)/cAMP pathway. On that basis, the experiment in vivo was conducted in this experiment. Eighty Wistar rats were orally exposed to 0 (control group); 0.4 mg/mL (low-dose group); 0.8 mg/mL (mid-dose group) and 1.6 mg/mL (high-dose group) AlCl3 for 120 days, respectively. Aluminum (Al), NE, macrophage migration inhibitory factor (MIF) and tumor necrosis factor-α (TNF-α) contents in serum, cAMP content, β2 -AR density, mRNA expressions of TNF-α, MIF and β2 -AR in rat peritoneal macrophages were examined. These results showed that AlCl3 increased serum Al and NE contents, peritoneal macrophages cAMP content, the density and mRNA expression of the β2 -AR, and decreased serum MIF and TNF-α contents, peritoneal macrophages mRNA expressions of MIF and TNF-α. Serum NE content was negatively correlated with serum TNF-α and MIF contents and peritoneal macrophages mRNA expressions of TNF-α and MIF, but positively correlated with cAMP content, density of β2 -AR and mRNA expression of β2 -AR of peritoneal macrophages. It indicated that AlCl3 suppresses peritoneal macrophages function of rats through β2 -AR/cAMP pathway acted by NE. Highlights: Aluminum trichloride (AlCl3 ) promoted the release of norepinephrine (NE). AlCl3 activated the β2 -adrenoceptors/cAMP pathway in vivo . NE played an important role in the β2 -AR/cAMP pathway acted with AlCl3 .